MENANAMKAN NILAI-NILAI RELLIGIUS MELALALUI PELAKSANAAN SHOLAT DHUHA DI MIN 4 REJANG LEBONG - Debi Irama; Ifnaldi ifnaldi; Maria Botifar (UIN Fatmawati Sukarno Bengkulu, 2021)
The aim of this research is to find out how MIN 4 Rejang Lebong teachers try to instill religious valuesin their students. Therefore, in this research the author used a qualitative descriptive research type and this research was conducted at MIN 4 Rejang Lebong and the data obtained was obtained through observation, interviews and documentation. From the results of this research, MIN 4 Rejang Lebong's efforts to instill the value of religiosity through the habit of Duha prayers have had a positive impact, and the benefit of getting used to Duha prayers is that these valuesgradually become more important for students. student. This means that the value of religiosity is transmitted by several students who are already aware of praying and are starting to get used to performing sunnah and obligatory prayers. However, there are still obstacles in carrying out the Dhuha prayer, namely that it takes a long time to condition the students.